2018
DOI: 10.2220/biomedres.39.179
|View full text |Cite
|
Sign up to set email alerts
|

<b>Intracellular localization of GGA accessory protein p56 in cell lines and central nervous system neur</b><b>ons </b>

Abstract: Adaptor protein complex-1 (AP-1) and Golgi associated, γ-adaptin ear containing, Arf binding proteins (GGAs) are clathrin adaptors that regulate membrane trafficking between the trans-Golgi network (TGN) and endosomes. p56 is a clathrin adaptor accessory protein that may modulate the function of GGAs in mammalian cell lines. However, the precise relationship between p56 and the three GGAs (GGA1-3), as well as the physiological role of p56 in tissue cells, remain unknown. To this end, we generated an antibody a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Recently, it was shown that GGAs and the related clathrin adaptor AP-1 complex have functions not only in TGN-endosomal/lysosomal membrane trafficking, but also for the surface expression of a series of integral membrane proteins, including Notch and the epidermal growth factor receptor [ 13 , 21 ]. Moreover, Conejo et al reported that insulin and insulin-like growth factors signaling play significant roles in the maturation of myotubes [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, it was shown that GGAs and the related clathrin adaptor AP-1 complex have functions not only in TGN-endosomal/lysosomal membrane trafficking, but also for the surface expression of a series of integral membrane proteins, including Notch and the epidermal growth factor receptor [ 13 , 21 ]. Moreover, Conejo et al reported that insulin and insulin-like growth factors signaling play significant roles in the maturation of myotubes [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The GGA family proteins are well known for their functions in recognition of cargo proteins that are sorted at the TGN; therefore, we initially speculated that GGA1 was involved in the sorting of fusion machinery to the plasma membrane. Indeed, a recent report showed that GGA2 has a crucial role in the cell surface expression of the epidermal growth factor receptor (EGFR), and the GGA-related clathrin adaptor AP-1 complex is also involved in targeting of the cell surface signaling molecule Notch and the secretion of certain soluble factors [ 13 , 21 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last two decades, numerous publications of the GGA proteins in tissue culture cells have identified a myriad of binding partners and functions for these monomeric clathrin adaptors [2]. Employing siRNA targeting the individual GGAs, some studies have attributed distinct roles for each GGA [21][22][23], while other studies have found overlapping roles [24,25], or even antagonizing roles [26], depending on the pathway that was being studied. In addition, our analysis of Gga null mice revealed a non-redundant physiological role for the three orthologs in rodents [27].…”
Section: Discussionmentioning
confidence: 99%